Alcohol Abuse and HIV Infection: Role of DRD2 - Agudelo, Marisela (Curr HIV Res, 2014)
According to a survey from the HIV Cost and Services Utilization Study (HCSUS), approximately 53% of HIV-infected patients reported drinking alcohol and 8% were classified as heavy drinkers. The role of alcohol as a risk factor for HIV infection has been widely studied and recent research has found a significant association between heavy alcohol consumption and lower levels of CD4 T cells among HIV-infected alcoholics. Although there is evidence on the role of alcohol as a risk factor for HIV transmission and disease progression, there is a need for population studies to determine the genetic mechanisms that affect alcohol’s role in HIV disease progression. One of the mechanisms of interest is the dopaminergic system. To date, the effects of dopamine on HIV neuroimmune pathogenesis are not well understood; however, dopaminergic neural degeneration due to HIV is known to occur by viral invasion into the brain via immune cells, and modulation of dopamine in the CNS may be a common mechanism by which different types of substances of abuse impact HIV disease progression. Although previous studies have shown an association of D(2) dopamine receptor (DRD2) polymorphisms with severity of alcohol dependence, the expression of this allele risk on HIV patients with alcohol dependence has not been systematically explored. In the current study, DRD2 Taq1A and C957T SNP genotyping analyses were performed in 165 HIV-infected alcohol abusers and the results were examined with immune status and CD4 counts.